Learning from REDD+: a response to Fletcher et al. - Angelsen, Arild; Brockhaus, Maria; Duchelle, Amy E.; Larson, Anne; Martius, Christopher; Sunderlin, William D.; Verchot, Louis V.; Wong, Grace Y.; Wunder, Sven (Wiley, 2017)
Although REDD+ is approaching its 10th anniversary, major impacts in terms of reduced forest loss are hard to document. Conservation practitioners and scholars are therefore increasingly asking why REDD+ has not delivered more tangible results. A recent Comment in Conservation Biology by Fletcher et al. (2016) addresses this question. We agree with Fletcher et al. that REDD+ has been hyped in some circles, which has created unrealistic expectations among policy makers and forest dwellers alike. Yet, we argue that Fletcher et al. put forward an incomplete interpretation of the evolving REDD+ concept and practice and wrongly place the responsibility for lack of progress on the principles of payment for environmental services (PES) and on reliance on market-based instruments (MBIs), in part based on their misunderstanding of the PES concept.